2013
DOI: 10.1007/s11356-013-1809-4
|View full text |Cite
|
Sign up to set email alerts
|

Biota–sediment accumulation factor (BSAF), bioaccumulation factor (BAF), and contaminant levels in prey fish to indicate the extent of PAHs and OCPs contamination in eggs of waterbirds

Abstract: Samples of pond sediment, fish, and shrimp were collected from the Ramsar site at Mai Po marshes, Hong Kong (south China), and samples of pond sediment, fish, and shrimp, as well as eggs of water birds (Chinese Pond Herons (Ardeola bacchus) and Little Egrets (Egretta garzetta)), were collected from two smaller wetland sites at Jiangsu Province (mid-China), between 2004 and 2007. Accumulation levels of polycyclic aromatic hydrocarbons (PAHs) and organochlorine pesticides (OCPs) in the biota were used to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…from Mai Po (a Ramsar site) in Hong Kong, China. Domestic and industrial effluent discharged in the Pearl River Delta, have been a principal pollution source of this Ramsar site [54]. For DDD values ranged from ND to 14.83 ng/g ww, maximum value was detected in Exopalaemon modestus from Qiantang River, China.…”
Section: Occurrence Of Pollutants In Shrimpsmentioning
confidence: 94%
See 2 more Smart Citations
“…from Mai Po (a Ramsar site) in Hong Kong, China. Domestic and industrial effluent discharged in the Pearl River Delta, have been a principal pollution source of this Ramsar site [54]. For DDD values ranged from ND to 14.83 ng/g ww, maximum value was detected in Exopalaemon modestus from Qiantang River, China.…”
Section: Occurrence Of Pollutants In Shrimpsmentioning
confidence: 94%
“…Moreover, the shrimps sampled in estuary regions seem to be the mo contaminated ones [24,36,54,60,106,109,117]. For the PAHs evaluation the number of samples analysed varied between 3 [54,116,117,119,120] and 10 [24], the number of individuals collected ranged between 10 [117] and 300 [24]. The number of specimens pooled per sample ranged between 7 [109] and 200 [120].…”
Section: Occurrence Of Pollutants In Shrimpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis were conducted in triplicate (n = 3) with error of all analysis were within ±20 %. Data analysis BAF (bioaccumulation factors) were calculated as the ratio of concentration in biota to sediment [17,18] using the formula stated below:…”
Section: Measurement Using Lc-ms/ms-esimentioning
confidence: 99%
“…Mid-range values were observed in medium-sized herbivorous fish species (M. amblycephala). It has been suggested that bottom-dwelling omnivorous species that feed on suspended solids and/or sediments, such as molluscs (C. chinensis) and mud carp (C. carpio), may accumulate greater concentrations of contaminants (Zhou et al, 1998;Zhou and Wong, 2000;Leung et al, 2010;Kwok et al, 2013) and that species that feed on algae and zooplankton, such as P. hyalocranius and shrimp (L. modestus), may accumulate contaminants to a lesser degree (Zhou and Wong, 2000).…”
Section: The Bioaccumulation Of Ocps In Aquatic Biotamentioning
confidence: 99%